Late removal of retrievable caval filters (Swiss Medical Weekly, 2014)
The advent of retrievable caval filters was a game changer in the sense, that the previously irreversible act of implanting a medical device into the main venous blood stream of the body requiring careful evaluation of the pros and cons prior to execution suddenly became a “reversible“ procedure where potential hazards in the late future of the patient lost most of their weight at the time of decision making. This review was designed to assess the rate of success with late retrieval of so called retrievable caval filters in order to get some indication about reasonable implant duration with respect to relatively “easy“ implant removal with conventional means, i.e., catheters, hooks and lassos. A PubMed search ( http://www.pubmed.gov ) was performed with the search term „cava filter retrieval after 30 days clinical“, and 20 reports between 1994 and 2013 dealing with late retrieval of caval filters were identified, covering approximately 7,000 devices with 600 removed filters. The maximal duration of implant reported is 2,599 days and the maximal implant duration of removed filters is also 2,599 days. The maximal duration reported with standard retrieval techniques, i.e., catheter, hook and/or lasso, is 475 days, whereas for the retrievals after this period more sophisticated techniques including lasers, etc. were required. The maximal implant duration for series with 100% retrieval accounts for 84 days, which is equivalent to 12 weeks or almost 3 months. We conclude that retrievable caval filters often become permanent despite the initial decision of temporary use. However, such “forgotten“ retrievable devices can still be removed with a great chance of success up to three months after implantation. Conventional percutaneous removal techniques may be sufficient up to sixteen months after implantation whereas more sophisticated catheter techniques have been shown to be successful up to 83 months or more than seven years of implant duration. Tilting, migrating, or misplaced devices should be removed early on, and replaced if indicated with a device which is both, efficient and retrievable.